Experiences at University: Perceptions of students with disabilities - Duquette, Cheryll (Canadian Journal of Higher Education, 2000)
Using Tinto's (1975) model of dropping out or persisting, this study examined the perceived experiences at university of students with disabilities. Tinto's (1975) model presents three variables which are related to persistence: background characteristics, integration into the academic milieu, and social integration. Thirty-six students completed a questionnaire, and of this group 17 participated in a narrative interview. Later, six of these people engaged in a focus group. The findings of this study showed that background characteristics and academic integration were more important variables related to persistence than social integration. Goal commitment, support of family and friends and understanding professors were found to be important elements related to persisting among these students with disabilities.